Synchronization of Codification of Unspecified Schizophrenia Againts Back-Referral System of Mirit Public Health Center - Nur Hayati Munawaroh; Ndari Afriyani; Sri Wahyuni; Triyo Rachmadi (Universitas Ahmad Dahlan, 2021)
Background: The disease classification system is a grouping of diseases following the International Statistical Classification of Diseases and Related Health Problems Tenth Revisions ICD-10. The coding application must be in accordance with ICD-10 to obtain a valid code in disease indexing, national, international reporting of morbidity and mortality, analysis of health care costs, and epidemiological and clinical research. The diagnosis of schizoaffective disorder is made if schizophrenia and affective disorder are symptoms based on the ICD-10 diagnostic criteria. This study aims to determine the synchronization of the codification of unspecified schizophrenia and determine the factors that influence it against the back-referral system at the Mirit Health Center. Method: This research is qualitative research with a descriptive approach. Respondents were four officers, i.e. one doctor, one medical record officer, one person holding a mental program, one pharmacy officer. The number of observed medical record documents was 96 data with research indicators of accuracy and completeness of the diagnosis code in patients referred from First Level Health Facilities (FKTP) to Advanced Health Facilities (FKTL). Result: The results showed 30 referrals, with nine referrals having the accuracy of the patient referral diagnosis code. The back-referral program (PRB) for mental illness at the Mirit Health Center, in collaboration with Mbah Marsio's mental health rehabilitation center, was carried out well. However, the implementation of the Chronic Disease Management program (Prolanis) for mental health was still not good. Conclusion: There are many unsynchronized codifications. It is recommended to conduct an evaluation where they communicate with each other about the patient's condition to supervise the implementation of Referback Patients, especially to specialists who write the back-referral form.